Review of Wastewater Treatment Technologies in View of their Application in the DR Congo Mining Industry - Shengo Lutandula, Michel; Ilunga Mpanga, Fabien (The Global Environmental Engineers, 2021)
The world is currently experiencing a water crisis in terms of both quantity and quality due to water ever-growing demand in large-scale consumer sectors such as agriculture, industry and tourism. This crisis results from the increasing pressure on water resources brought about the world population growth, continued urbanization and rapid industrialization as sources of an increased release of contaminated water into watercourses. Faced with this worrying situation, strategies have been developed throughout the world for improving both the availability and access to water. Different technologies, both established and emerging ones, are utilized in view to treat wastewaters, including those of the mining origin. The present work reviews the different uses of water in the mining industry and identifies its different sources of polluted water. It analyses some wastewater treatment techniques and their applicability in the reclamation of wastewater generated by the DR Congo mining industry. The adopted approach, in dealing with the relevant issue of water crisis experienced worldwide in terms of both quantity and quality, is expected to help improving practices in the management of wastewater of mining origin, increasing access to water and its sustainable use.